Prostate specific antigen enhances the innate defence of prostatic epithelium against Escherichia coli infection. Issue 14 (1st July 2013) - Townes, Claire L; Ali, Ased; Gross, Naomi; Pal, Deepali; Williamson, Stuart; Heer, Rakesh; Robson, Craig N; Pickard, Robert S; Hall, Judith
Abstract BACKGROUND This study investigated whether the increase in serum prostate specific antigen (PSA) typically seen during male urinary tract infection (UTI) is incidental or reflects an innate defence mechanism of the prostate. The protective roles of the whey‐acid‐motif‐4‐disulphide core (WFDC) proteins, secretory leukoproteinase inhibitor (SLPI) and WFDC2, in the prostate were also examined. METHODS UTI recurrence was assessed retrospectively in men following initial UTI by patient interview. PSA, SLPI, and WFDC2 gene expression were assessed using biopsy samples. LNCaP and DU145 in vitro prostate cell models were utilized to assess the effects of an Escherichia coli challenge on PSA and WFDC gene expression, and bacterial invasion of the prostate epithelium. The effects of PSA on WFDC antimicrobial properties were studied using recombinant peptides and time‐kill assays. RESULTS Men presenting with PSA >4 ng/ml at initial UTI were less likely to have recurrent (r) UTI than those with PSA <4 ng/ml [2/15 (13%) vs. 7/10 (70%), P < 0.01]. Genes encoding PSA, SLPI and WFDC2, were expressed in prostatic epithelium, and the PSA and SLPI proteins co‐localized in vivo. Challenging LNCaP (PSA‐positive) cells with E. coli increased PSA, SLPI, and WFDC2 gene expression (P < 0.05), and PSA synthesis (P < 0.05), and reduced bacterial invasion. Pre‐incubation of DU145 (PSA‐negative) cells with PSA also decreased bacterial invasion. In vitro incubation of recombinant SLPI and WFDC2 with PSA resulted in peptide proteolysis and increased E. coli killing. CONCLUSIONS Increased PSA during UTI appears protective against rUTI and in vitro is linked to proteolysis of WFDC proteins supporting enhanced prostate innate defences. Prostate 73: 1529–1537, 2013. © 2013 Wiley Periodicals, Inc.